Сучасні інформаційні технології та методи інтернет-брендингу студентської організації - Михайлишин, Анастасія; Федушко, Соломія (Видавництво Львівської політехніки, 2016)
In this paper the usage of modern information technologies and methods in popularization of student organization is investigated. The personal page of student organization in the social network Facebook is created and website is designed for online–branding purposes.
Keywords: інтернет-брендинг; WWW; PR-технології; інформаційний ресурс; студентська організація; соціальна мережа; SMM